Comparison of breeding strategies of two sympatric thrush species in an alpine environment - Gao, Yulin; Xiao, Hongqiang; Han, Han; Wei, Wei; Zhou, Hong; Zhang, Zejun (Frontiers in Ecology and Evolution, 2022)
Closely related birds that occur sympatrically will inevitably differ in the acquisition of food resources, nest site selection, and breeding times. The successful coexistence of birds that breed in the same area can be determined by investigating how they divide limited resources and reduce interspecific competition. Our study area is located at the eastern foot of the Qinghai-Tibet Plateau, with a high altitude and low annual average temperature. In this study, the life history characteristics and reproductive ecological parameters of two closely related species, the Chestnut Thrush (Turdus rubrocanus) and the Kessler’s Thrush (Turdus kessleri), were compared in detail in April-July of 2020, 2021, and 2022 in the scrub along the Liqiu River in Xinduqiao Town, Tibetan Autonomous Prefecture of Garzê, Sichuan. The results showed no differences in nesting material, nest cup size, clutch size, feeding strategy of nestlings, brood food type, and reproductive effectiveness between the Chestnut Thrush and the Kessler’s Thrush. However, the Kessler’s Thrush had a higher nesting height, thicker nest wall, earlier breeding time, smaller eggs, fewer brooding frequent and a longer brooding time compared to the Chestnut Thrush. In addition, they invested more time in parental care, resulting in a faster growth and development rate. The results indicate that birds with different ranges and breeding in the same range show convergent and divergent life history characteristics in terms of reproductive biology. Chestnut Thrush with low reproductive altitude shows the characteristics of low-altitude bird reproduction in part of reproductive biology, while Kessler’s Thrush with high reproductive altitude shows the characteristics of high-altitude bird reproduction in part of reproductive biology.